Exoscope and operative microscope for training in microneurosurgery: A laboratory investigation on a model of cranial approach - Calloni, Tommaso; Antolini, Laura; Roumy, Louis-Georges; Nicolosi, Federico; Carrabba, Giorgio G.; Di Cristofori, Andrea; Fontanella, Marco M.; Giussani, Carlo G. (Frontiers in Surgery, 2023)
Abstract Objective To evaluate the viability of Exoscopes in the context of neurosurgical education and compare the use of a 4k3D exoscope to a traditional operative microscope in the execution of a task a task of anatomic structure identification on a model of cranial approach. Material and methods A cohort of volunteer residents performed a task of anatomical structure identification with both devices 3 times across an experimental period of 2 months. The execution of the task was timed and the times achieved were analysed. The volunteers answered two questionnaires concerning their opinions of the two devices. Results Across tries, the efficiency in task execution improved for the whole cohort. The exoscope appeared superior in identifying a single anatomical structure starting from outside the surgical field when deep structures were included in the pool of structures to identify. In all other settings, the two devices did not differ in a statistically significant manner. The volunteers described the exoscope as superior to the microscope in all the aspects we inquired about in the questionnaires besides the depth of field perception, which they felt to be better on the microscope. Volunteers furthermore showed overwhelming support for training on different devices and with model of surgical approaches. Conclusions The exoscope appeared to be non-inferior to the microscope in the execution of a task of timed identification of anatomical structures on a model of cranial approach carried out by our cohort of residents. In the questionnaires, the residents reported the exoscope to be superior to the microscope in 8 of 9 investigated domains. Further studies are needed to investigate exoscope use in learning of microsurgical skills.